Steiner Wiener Index of Certain Windmill Graphs. - Herish Omer Abdullah (Zanco Journal of Pure and Applied Sciences, 2023)
For a connected graph of order and a non-empty subset , the - Steiner distance of is defined to be the smallest size among all connected subgraphs whose vertex sets contain . In this paper, we obtain the Hosoya polynomials of Steiner -distance of some windmill graphs. Moreover, the Steiner Wiener indices of certain windmill graphs are also obtained.